The Effectiveness of Technology to Improve Educational Counseling Services: A Systematic Literature Review - Muhammad, Rifqi (Journal of Teaching and Learning, 2024)
There is a scarcity of research that documents the use of technology-based educational counseling services specifically targeting students. This study’s aim is to compile and conduct a comprehensive review of the literature on the efficacy of technology in enhancing educational counseling services. Searches were conducted using the Publish or Perish (PoP) method throughout, along with Scopus, Crossref, PubMed, ACA, Web of Science, Springer, Emerald, as well as the Taylor and Francis databases. Data gathering was done in October and November 2023. The evaluation included a total of 19 papers, and the results indicated that technology has been proven to improve educational counseling services, where it is used in mental health that is dominated by MHAs, mobile well-being apps, mHEALTH, SMS, FER, and mindfulness apps. Computer-assisted and CD-ROM tools are used in personal counseling, while CAI is used in providing learning counseling. Social counseling used two technologies: a safety decision-aid smartphone app and a virtual message app. Counseling for learning was used with CAI, MCO, and video modeling. Career counseling employed a mobile-based career counseling app along with career counseling websites. The investigation included the countries of Indonesia, the United States, the United Kingdom, Türkiye (Turkey), the Philippines, and Iran.